Piano Sonatas - Beethoven, Ludwig van. 1770-1827
Handel: 1.- Concerto No. 4 in D minor 2.- Concerto No. 5 in G minor 3.- Concerto No. 6 in B flat major Bach: 4.- Praeludium and fugue in C major 5.- Praeludium and fugue in E minor